2020
DOI: 10.9734/ajahr/2020/v5i330053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium on the Growth, Yield and Physico-chemical Properties of Three Garden Pea (Pisum sativum) Varieties

Abstract: An experiment was conducted at the Horticulture Research Farm, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh during November 2015 to March 2016 to find out the effects of potassium on the growth, yield and physico-chemical properties of three garden pea (Pisum sativum) varieties. The experiment comprise three Garden pea varieties viz. V1 = IPSA Motorshuti-3, V2 = Broad Bean Master Piece and V3 = BARI Motorshuti-1 and four levels of potassium viz. K0 (Control), K1 (25 kg ha-1), K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…W here, phosphorus promotes reproductive growth, leading to higher pod yield, longer pods, more grains and more pods per plant Husain et al (2019) and potassium is crucial for plan t energy status, assimilate transloc ation and maintenance of tissue water relations. The results are in conformity with Akter et al (2020). W hen combined with nitrogen, phosphorus and potassium (NPK), these nutrients promote overall plant growth characteristics.…”
Section: Effect Of Weather Conditionssupporting
confidence: 75%
“…W here, phosphorus promotes reproductive growth, leading to higher pod yield, longer pods, more grains and more pods per plant Husain et al (2019) and potassium is crucial for plan t energy status, assimilate transloc ation and maintenance of tissue water relations. The results are in conformity with Akter et al (2020). W hen combined with nitrogen, phosphorus and potassium (NPK), these nutrients promote overall plant growth characteristics.…”
Section: Effect Of Weather Conditionssupporting
confidence: 75%
“…Similarly, Huda et al, [30] observed that increasing the potassium level from 48 to 96 kg K 2 O/fed gradually and significantly increased green pod yields of green bean. Akter et al, [31] also recorded the highest number of green pods plant -1 (27.22), number of seeds pod -1 (8.00) and green pod yield (10.66 t ha -1 ) garden pea from the crop fertilized with 50 kg K 2 O ha -1 .…”
Section: Effect Of Potassium On the Yield Contributing Characters Andmentioning
confidence: 92%
“…The improvement of the physical properties of the soil as a result of the use of strip-tillage, confirmed by the studies of Fernández et al [44], Moraru et al [45], and Stankowski et al [46], may also be of some importance. K in legumes is necessary for the proper synthesis of protein-building amino acids and it is involved in the construction of tissues that ensure the mechanical stability of plants and supports seed formation [47]. In our study, 3 weeks after sowing as well as before harvesting, the K content in the 0-20 cm soil layer was higher under strip-tillage compared to plowing.…”
Section: Discussionmentioning
confidence: 45%